Academic Senate Minutes 2005-02-24 - Academic Senate:::::::::
Agenda approved. Minutes delayed. Chair's report. Course Outline Policy referred back to FSAC. Revision to Cheating and Plagiarism policy approved. Posthumous Degree request from Modern Languages for Allan Stone approved. Spring Elections approved to go forward. Update on WASC. President's report. Provost's report. Statewide Senator's report. SAC report. Announcements.